Diabetic Mastopathy Coexisting with Appendix Neuroendocrine Tumor in A Type 1 Diabetic Woman: A Case Report - Sareri, Gabriele Iraci; Cataldo, Dorica; Mancini, Virginia; Nigi, Laura; Dotta, Francesco (Archives of Clinical and Medical Case Reports, 2022)
Diabetic mastopathy is a rare condition representing less than 1% of all benign breast lesions, occurring preferentially in pre-menopausal women affected by long-standing type 1 diabetes, especially in presence of microvascular diabetic complications. Its exact etiopathogenesis is still unclear, however an autoimmune background is highly hypothesized. In some cases, diabetic mastopathy strongly mimicks breast cancer. To date, no widely accepted diagnostic guidelines have been established for this pathological condition, however core-needle biopsy represents the gold standard for diagnosis. Surgical excision is the primary treatment option, taking into consideration the potential development of diabetic mastopathy into a breast cancer. We here describe for the first time the coexistence of diabetic mastopathy with a neuroendocrine tumor in a long-standing type 1 diabetic woman. This association apparently seems “incidental”, however it would be interesting to verify whether other cases will be reported in order to clarify the possible relationship between these two pathological conditions.